Environmentally friendly, non-toxic, biodegradable garbage bag and preparation method thereof

By using a variety of polymer materials and nanomaterials, combined with granulation and coextrusion and blowing film technology, environmentally friendly, non-toxic and biodegradable garbage bags with excellent performance were prepared, which solved the problems of non-degradability and insufficient performance of existing garbage bags. Fast, complete biodegradation and excellent environmental performance are achieved.

CN118852774BActive Publication Date: 2025-02-07金达科技股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411368585.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-07
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing garbage bag materials are non-degradable, and the huge amount of use leads to waste of resources and environmental pollution. They also lack performance and are difficult to meet market demand.

Method used

Polyethylene, nano-calcium carbonate, photosensitizer, chitosan, lubricant, dispersant, coupling agent, starch, acrylamide, polyvinyl alcohol, crosslinking agent, initiator, polyaspartic acid, polylactic acid, Polybutylene terephthalate-butylene adipicate, polybutylene succinate and other materials are prepared by granulation and co-extrusion and blowing film technology.

Benefits of technology

It improves the mechanical and biodegradable properties of garbage bags, has a fast degradation speed, can completely degrade into carbon dioxide, water and biomass in a natural environment, and has excellent environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118852774B_ABST
    Figure CN118852774B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of garbage packaging bags, and specifically discloses an environmentally friendly, non-toxic, biodegradable garbage bag and a preparation method thereof. The raw materials of the environmentally friendly, non-toxic, biodegradable garbage bag include, by mass: 80-90 parts of polyethylene, 100-120 parts of nano calcium carbonate, 1-5 parts of photosensitizer, 1-5 parts of chitosan, 1-5 parts of lubricant, 1-3 parts of dispersant, 1-3 parts of coupling agent, 10-30 parts of starch, 1-5 parts of acrylamide, 1-2 parts of polyvinyl alcohol, 0.01-0.1 parts of cross-linking agent, 0.001-0.01 parts of initiator, 1-5 parts of polyaspartic acid, 30-40 parts of polylactic acid, 40-60 parts of polybutylene terephthalate-adipate, 5-15 parts of polybutylene succinate, 0.1-2 parts of maleic anhydride, and 5-15 parts of toughening fiber; the raw materials of the toughening fiber include: oligosaccharides, sodium methyl methacrylate sulfonate, potassium persulfate, and microcrystalline cellulose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of garbage packaging bags, and in particular to an environmentally friendly, non-toxic and biodegradable garbage bag and a preparation method thereof. Background Art

[0002] Garbage bags are widely used because of their convenience and practicality. Currently, most of the garbage bags sold on the market are made of polyethylene or polyvinyl chloride. Due to the huge number of garbage bags used and their non-degradability, they not only cause serious waste of resources and waste, but also seriously pollute the soil. If they are incinerated, they will generate harmful smoke and toxic gases, which will pollute the environment for a long time.

[0003] With the improvement of people's living standards, environmentally friendly, non-toxic and biodegradable garbage bags have gradually entered people's lives in recent years. Biodegradable polymer materials are made from natural polymers (such as starch, cellulose, chitin) and agricultural and sideline products through microbial fermentation / synthesis of biodegradable polymers, but this type of material has poor mechanical properties and insufficient mechanical strength, which makes it difficult to meet market demand.

[0004] The raw materials for the fully biodegradable plastic bags currently used in the market are mostly polylactic acid (PLA), polybutylene terephthalate-adipate (PBAT), polybutylene succinate (PBS) and other materials. They are not only expensive, but also have performance far inferior to traditional plastics. Especially when used as garbage bags, they often have problems such as tearing and leakage, and cannot be promoted for use. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an environmentally friendly, non-toxic, biodegradable garbage bag and a preparation method thereof.

[0006] An environmentally friendly, non-toxic, biodegradable garbage bag, the raw materials of which include, by weight: 80-90 parts of polyethylene, 100-120 parts of nano calcium carbonate, 1-5 parts of photosensitizer, 1-5 parts of chitosan, 1-5 parts of lubricant, 1-3 parts of dispersant, 1-3 parts of coupling agent, 10-30 parts of starch, 1-5 parts of acrylamide, 1-2 parts of polyvinyl alcohol, 0.01-0.1 parts of crosslinking agent, 0.001-0.01 parts of initiator, 1-5 parts of polyaspartic acid parts, polylactic acid 30-40 parts, polybutylene terephthalate-adipate 40-60 parts, polybutylene succinate 5-15 parts, maleic anhydride 0.1-2 parts, toughening fiber 5-15 parts; the raw materials of toughening fiber include: oligosaccharide, sodium methacrylate sulfonate, potassium persulfate, microcrystalline cellulose, and the mass ratio of oligosaccharide, sodium methacrylate sulfonate, potassium persulfate, and microcrystalline cellulose is 5-15:1-2:0.01-0.1:10-20.

[0007] Preferably, the particle size of nano calcium carbonate is 60-80 nm.

[0008] Preferably, the photosensitizer is at least one of ferric eleostearate, benzophenone and ferric stearate.

[0009] Preferably, the lubricant is at least one of calcium stearate, zinc stearate and magnesium stearate.

[0010] Preferably, the dispersant is erucamide and / or polyethylene wax.

[0011] Preferably, the coupling agent is at least one of a titanate coupling agent, an aluminate coupling agent, and a silane coupling agent.

[0012] Preferably, the crosslinking agent is N,N-methylenebisacrylamide, and the initiator is ammonium persulfate.

[0013] Preferably, the toughened fiber is prepared by the following specific operation: adding oligosaccharides to water, stirring evenly at 60-75°C, adding sodium methyl methacrylate sulfonate thereto and continuing stirring for 10-20 minutes, adding potassium persulfate, adjusting the pH value of the system to 7-7.8, stirring for 1-4 hours, adding microcrystalline cellulose, stirring at 90-100°C for 10-30 minutes, filtering, washing to neutrality, and freeze-drying.

[0014] The method for preparing the above-mentioned environmentally friendly, non-toxic and biodegradable garbage bag comprises the following steps:

[0015] S1. Add starch to water and ultrasonically treat for 1-2 hours, introduce nitrogen for degassing, add acrylamide, polyvinyl alcohol, crosslinking agent, initiator, polyaspartic acid, stir at 70-80° C. for 1-3 hours, filter, wash with water, vacuum dry, add polyethylene, nano calcium carbonate, photosensitizer, chitosan, lubricant, dispersant, coupling agent, mix and stir for 1-3 hours, and granulate to obtain inner layer granules;

[0016] S2, vacuum drying polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride for 10-12 hours to remove moisture and impurities, adding toughening fiber and mixing for 1-3 hours, and granulating to obtain outer layer pellets;

[0017] S3, conveying the inner layer pellets and the outer layer pellets to two feed ports of the co-extrusion film blowing system respectively for extrusion film blowing.

[0018] Preferably, the co-extrusion film blowing system comprises two single-screw extruders and an A / B / A film blowing head, the melt flow of the outer layer pellets is divided into two parts, which are combined with the inner layer pellets before the film blowing die to obtain a three-layer composite film; the heating zone temperature of the co-extrusion film blowing system is 160-180°C, and the temperature of the film blowing head is 145-155°C. Beneficial Effects

[0019] 1. The present invention adopts starch, acrylamide and polyvinyl alcohol for cross-linking, which can not only effectively improve the mechanical properties of starch, but also cooperate with polyaspartic acid to effectively retain the hydrophilicity of the product, and the product has good plasticity and high compatibility with polyethylene. The inner layer granules are then prepared by granulation, which not only retains the physical properties of polyethylene and has excellent tensile strength, but also has excellent biodegradability. With the biodegradation of starch, the polyethylene modified material disintegrates into fragments, effectively accelerating its degradation rate.

[0020] 2. Using potassium persulfate as an initiator, oligosaccharides are combined with sodium methyl methacrylate sulfonate, and the sulfonic acid groups on them can be grafted with the hydroxyl groups of microcrystalline cellulose, and the resulting toughened fibers have good hydrophilicity; using polylactic acid, polybutylene terephthalate-adipate, and polybutylene succinate as base materials, they have good binding performance with the toughened fibers under the action of maleic anhydride, and the long-chain molecular chains are combined to form intricate hybrid molecular chains, which improves its tensile strength while also giving the garbage bag good flexibility and excellent puncture resistance.

[0021] 3. The present invention adopts outer layer granular material and inner layer granular material to prepare garbage bags in coordination. The outer layer structure quickly infiltrates when absorbing water, and cooperates with the inner layer pretreated starch to have good mutual conduction performance, so that the obtained garbage bags have excellent biodegradability after being discarded, and the degradation speed is fast. They can be degraded into carbon dioxide, water and biomass under natural environment conditions, and have excellent environmental protection performance.

[0022] The experiment proves that the garbage bag obtained by the present invention can reach a degradation rate of more than 50% after only 43 days of composting, and has excellent degradation performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a photo of the environmentally friendly, non-toxic, biodegradable garbage bag obtained in Example 5.

[0024] Figure 2 The tensile strength comparison chart of the garbage bags obtained in Example 5 and Comparative Examples 1-2 is shown.

[0025] Figure 3 It is a comparison chart of the puncture strength of the garbage bags obtained in Example 5 and Comparative Examples 1-2.

[0026] Figure 4 The figure is a comparison chart of the load-bearing qualities of the garbage bags obtained in Example 5 and Comparative Examples 1-2.

[0027] Figure 5 This is a photo of the environmentally friendly, non-toxic, biodegradable garbage bag obtained in Example 5 mixed with soil.

[0028] Figure 6 This is a photo of the environmentally friendly, non-toxic, biodegradable garbage bag obtained in Example 5 mixed with soil and degraded by composting for 150 days.

[0029] Figure 7 The time-biodegradation percentage curve of the environmentally friendly, non-toxic, biodegradable garbage bag obtained in Example 5 and the reference material is shown.

[0030] Figure 8 The graph is a time-cumulative carbon dioxide generation curve of the environmentally friendly, non-toxic, biodegradable garbage bag obtained in Example 5, the reference material, and the blank control. DETAILED DESCRIPTION

[0031] The present invention will be further explained below in conjunction with specific embodiments. Example 1

[0032] The invention discloses an environmentally friendly, non-toxic and biodegradable garbage bag. The raw materials thereof include: 80 kg of polyethylene, 100 kg of nano calcium carbonate with a particle size of 60-80 nm, 1 kg of ferrous eleostearate, 1 kg of chitosan, 1 kg of calcium stearate, 1 kg of erucic acid amide, 1 kg of aluminate coupling agent DL-411, 10 kg of corn starch, 1 kg of acrylamide, 1 kg of polyvinyl alcohol, 10 g of N,N-methylenebisacrylamide, 1 g of ammonium persulfate, 1 kg of polyaspartic acid, 30 kg of polylactic acid, 40 kg of polybutylene terephthalate-adipate, 5 kg of polybutylene succinate, 100 g of maleic anhydride and 5 kg of toughening fiber.

[0033] The toughened fiber was prepared by the following specific operation: adding trehalose to water, stirring evenly at 60°C, adding sodium methyl propylene sulfonate to it and continuing to stir for 10 minutes, adding potassium persulfate, adjusting the pH value of the system to 7-7.8, stirring for 1 hour, adding microcrystalline cellulose, stirring at 90°C for 10 minutes, filtering, washing to neutrality, and freeze-drying. The mass ratio of trehalose, sodium methyl propylene sulfonate, potassium persulfate, and microcrystalline cellulose is 5:1:0.01:10.

[0034] The method for preparing the above-mentioned environmentally friendly, non-toxic and biodegradable garbage bag comprises the following steps:

[0035] S1. Add corn starch to 100 kg of water and perform ultrasonic treatment for 1 hour at an ultrasonic frequency of 10 kHz. Pass nitrogen for degassing. Add acrylamide, polyvinyl alcohol, N,N-methylenebisacrylamide, ammonium persulfate, and polyaspartic acid thereto. Stir at 70° C. for 1 hour. Filter. Wash with deionized water. Vacuum dry. Add polyethylene, nano-calcium carbonate, ferrous eleostearate, chitosan, calcium stearate, erucic acid amide, and aluminate coupling agent DL-411. Mix and stir for 1 hour. Send to a twin-screw granulator for granulation to obtain inner layer pellets.

[0036] S2, polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride are dried at 50° C. in vacuum for 10 h to remove moisture and impurities, toughening fibers are added and mixed for 1 h, and then sent to a twin-screw granulator for granulation to obtain outer layer granules;

[0037] S3, conveying the inner layer pellets and the outer layer pellets to two feed ports of the co-extrusion film blowing system respectively for extrusion film blowing.

[0038] The above-mentioned co-extrusion film blowing system includes two single-screw extruders and an A / B / A film blowing head. The melt flow of the outer layer pellets is divided into two parts and combined with the inner layer pellets before the film blowing die to obtain a three-layer composite film; the heating zone temperature of the co-extrusion film blowing system is 160°C, and the temperature of the film blowing head is 145°C. Example 2

[0039] The invention discloses an environmentally friendly, non-toxic and biodegradable garbage bag. The raw materials thereof include: 90 kg of polyethylene, 120 kg of nano calcium carbonate with a particle size of 60-80 nm, 5 kg of benzophenone, 5 kg of chitosan, 5 kg of calcium stearate, 3 kg of polyethylene wax, 3 kg of aluminate coupling agent DL-411, 30 kg of corn starch, 5 kg of acrylamide, 2 kg of polyvinyl alcohol, 100 g of N,N-methylenebisacrylamide, 10 g of ammonium persulfate, 5 kg of polyaspartic acid, 40 kg of polylactic acid, 60 kg of polybutylene terephthalate-adipate, 15 kg of polybutylene succinate, 2 kg of maleic anhydride and 15 kg of toughening fiber.

[0040] The toughened fiber was prepared by the following specific operation: adding maltooligosaccharide to water, stirring evenly at 75°C, adding sodium methyl propylene sulfonate to it and continuing to stir for 20 minutes, adding potassium persulfate, adjusting the pH value of the system to 7-7.8, stirring for 4 hours, adding microcrystalline cellulose, stirring at 100°C for 30 minutes, filtering, washing to neutrality, and freeze-drying. The mass ratio of maltooligosaccharide, sodium methyl propylene sulfonate, potassium persulfate, and microcrystalline cellulose is 15:2:0.1:20.

[0041] The method for preparing the above-mentioned environmentally friendly, non-toxic and biodegradable garbage bag comprises the following steps:

[0042] S1. Add corn starch to 200 kg of water and ultrasonically treat for 2 hours at an ultrasonic frequency of 15 kHz, introduce nitrogen for degassing, add acrylamide, polyvinyl alcohol, N,N-methylenebisacrylamide, ammonium persulfate, and polyaspartic acid, stir at a temperature of 80°C for 3 hours, filter, wash with deionized water, vacuum dry, add polyethylene, nano-calcium carbonate, benzophenone, chitosan, calcium stearate, polyethylene wax, and aluminate coupling agent DL-411, mix and stir for 3 hours, and send to a twin-screw granulator for granulation to obtain inner layer pellets;

[0043] S2, polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride are dried at 80° C. in vacuum for 12 h to remove moisture and impurities, toughening fibers are added and mixed for 3 h, and then sent to a twin-screw granulator for granulation to obtain outer layer granules;

[0044] S3, conveying the inner layer pellets and the outer layer pellets to two feed ports of the co-extrusion film blowing system respectively for extrusion film blowing.

[0045] The above-mentioned co-extrusion film blowing system includes two single-screw extruders and an A / B / A film blowing head. The melt flow of the outer layer pellets is divided into two parts and combined with the inner layer pellets before the film blowing die to obtain a three-layer composite film; the heating zone temperature of the co-extrusion film blowing system is 180°C, and the temperature of the film blowing head is 155°C. Example 3

[0046] The invention discloses an environmentally friendly, non-toxic and biodegradable garbage bag. The raw materials thereof include: 82 kg of polyethylene, 115 kg of nano calcium carbonate with a particle size of 60-80 nm, 2 kg of ferrous eleostearate, 4 kg of chitosan, 2 kg of magnesium stearate, 2.5 kg of polyethylene wax, 1.5 kg of aluminate coupling agent DL-411, 25 kg of corn starch, 2 kg of acrylamide, 1.7 kg of polyvinyl alcohol, 20 g of N,N-methylenebisacrylamide, 7 g of ammonium persulfate, 2 kg of polyaspartic acid, 37 kg of polylactic acid, 45 kg of polybutylene terephthalate-adipate, 12 kg of polybutylene succinate, 800 g of maleic anhydride and 12 kg of toughening fiber.

[0047] The toughened fiber was prepared by the following specific operation: adding xylo-oligosaccharide to water, stirring evenly at 65°C, adding sodium methyl propylene sulfonate to it and continuing to stir for 18 minutes, adding potassium persulfate, adjusting the pH value of the system to 7-7.8, stirring for 2 hours, adding microcrystalline cellulose, stirring at 98°C for 15 minutes, filtering, washing to neutrality, and freeze-drying. Among them, the mass ratio of xylo-oligosaccharide, sodium methyl propylene sulfonate, potassium persulfate, and microcrystalline cellulose is 12:1.3:0.08:13.

[0048] The method for preparing the above-mentioned environmentally friendly, non-toxic and biodegradable garbage bag comprises the following steps:

[0049] S1. Add corn starch to 180 kg of water and ultrasonically treat for 80 min at an ultrasonic frequency of 13 kHz. Pass nitrogen for degassing. Add acrylamide, polyvinyl alcohol, N,N-methylenebisacrylamide, ammonium persulfate, and polyaspartic acid thereto. Stir at 73 ° C for 2.5 h. Filter. Wash with deionized water. Vacuum dry. Add polyethylene, nano-calcium carbonate, ferrous eleostearate, chitosan, magnesium stearate, polyethylene wax, and aluminate coupling agent DL-411 and mix and stir for 1.5 h. Send to a twin-screw granulator for granulation to obtain inner layer pellets.

[0050] S2, polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride are dried at 70° C. in vacuum for 10.5 h to remove moisture and impurities, toughening fibers are added and mixed for 2.5 h, and then sent to a twin-screw granulator for granulation to obtain outer layer granules;

[0051] S3, conveying the inner layer pellets and the outer layer pellets to two feed ports of the co-extrusion film blowing system respectively for extrusion film blowing.

[0052] The above-mentioned co-extrusion film blowing system includes two single-screw extruders and an A / B / A film blowing head. The melt flow of the outer layer pellets is divided into two parts and combined with the inner layer pellets before the film blowing die to obtain a three-layer composite film; the heating zone temperature of the co-extrusion film blowing system is 165°C, and the temperature of the film blowing head is 152°C. Example 4

[0053] The invention discloses an environmentally friendly, non-toxic and biodegradable garbage bag. The raw materials thereof include: 88 kg of polyethylene, 105 kg of nano calcium carbonate with a particle size of 60-80 nm, 4 kg of iron stearate, 2 kg of chitosan, 4 kg of magnesium stearate, 1.5 kg of polyethylene wax, 2.5 kg of titanate coupling agent NDZ-311, 15 kg of corn starch, 4 kg of acrylamide, 1.3 kg of polyvinyl alcohol, 80 g of N,N-methylenebisacrylamide, 3 g of ammonium persulfate, 4 kg of polyaspartic acid, 33 kg of polylactic acid, 55 kg of polybutylene terephthalate-adipate, 8 kg of polybutylene succinate, 1.6 kg of maleic anhydride and 8 kg of toughening fiber.

[0054] The toughened fiber was prepared by the following specific operation: adding xylo-oligosaccharide to water, stirring evenly at 70°C, adding sodium methyl propylene sulfonate to it and continuing to stir for 12 minutes, adding potassium persulfate, adjusting the pH value of the system to 7-7.8, stirring for 3 hours, adding microcrystalline cellulose, stirring at 92°C for 25 minutes, filtering, washing to neutrality, and freeze-drying. The mass ratio of xylo-oligosaccharide, sodium methyl propylene sulfonate, potassium persulfate, and microcrystalline cellulose is 8:1.7:0.02:17.

[0055] The method for preparing the above-mentioned environmentally friendly, non-toxic and biodegradable garbage bag comprises the following steps:

[0056] S1. Add corn starch to 120 kg of water and ultrasonically treat for 100 min at an ultrasonic frequency of 11 kHz. Pass nitrogen for degassing. Add acrylamide, polyvinyl alcohol, N,N-methylenebisacrylamide, ammonium persulfate, and polyaspartic acid thereto. Stir at 77 ° C for 1.5 h. Filter. Wash with deionized water. Vacuum dry. Add polyethylene, nano-calcium carbonate, iron stearate, chitosan, magnesium stearate, polyethylene wax, and titanate coupling agent NDZ-311. Mix and stir for 2.5 h. Send to a twin-screw granulator for granulation to obtain inner layer pellets.

[0057] S2, polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride were dried at 60° C. in vacuum for 11.5 h to remove moisture and impurities, toughening fibers were added and mixed for 1.5 h, and then sent to a twin-screw granulator for granulation to obtain outer layer granules;

[0058] S3, conveying the inner layer pellets and the outer layer pellets to two feed ports of the co-extrusion film blowing system respectively for extrusion film blowing.

[0059] The above-mentioned co-extrusion film blowing system includes two single-screw extruders and an A / B / A film blowing head. The melt flow of the outer layer pellets is divided into two parts, which are combined with the inner layer pellets before the film blowing die to obtain a three-layer composite film; the heating zone temperature of the co-extrusion film blowing system is 175°C, and the temperature of the film blowing head is 148°C. Example 5

[0060] The invention discloses an environmentally friendly, non-toxic and biodegradable garbage bag. The raw materials thereof include: 85 kg of polyethylene, 110 kg of nano calcium carbonate with a particle size of 60-80 nm, 3 kg of iron stearate, 3 kg of chitosan, 3 kg of magnesium stearate, 2 kg of polyethylene wax, 2 kg of titanate coupling agent NDZ-311, 20 kg of corn starch, 3 kg of acrylamide, 1.5 kg of polyvinyl alcohol, 50 g of N,N-methylenebisacrylamide, 5 g of ammonium persulfate, 3 kg of polyaspartic acid, 35 kg of polylactic acid, 50 kg of polybutylene terephthalate-adipate, 10 kg of polybutylene succinate, 1.2 kg of maleic anhydride and 10 kg of toughening fiber.

[0061] The toughened fiber was prepared by the following specific operation: chitosan oligosaccharide was added to water, stirred evenly at 68°C, sodium methyl propylene sulfonate was added thereto and stirred for 15 minutes, potassium persulfate was added, the pH value of the system was adjusted to 7-7.8, stirred for 2.5 hours, microcrystalline cellulose was added, stirred at 95°C for 20 minutes, filtered, washed to neutral, and freeze-dried. The mass ratio of chitosan oligosaccharide, sodium methyl propylene sulfonate, potassium persulfate, and microcrystalline cellulose was 10:1.5:0.05:15.

[0062] The method for preparing the above-mentioned environmentally friendly, non-toxic and biodegradable garbage bag comprises the following steps:

[0063] S1. Add corn starch to 150 kg of water and ultrasonically treat for 90 min at an ultrasonic frequency of 12 kHz. Pass nitrogen for degassing. Add acrylamide, polyvinyl alcohol, N,N-methylenebisacrylamide, ammonium persulfate, and polyaspartic acid thereto. Stir at 75 ° C for 2 h. Filter. Wash with deionized water. Vacuum dry. Add polyethylene, nano calcium carbonate, iron stearate, chitosan, magnesium stearate, polyethylene wax, and titanate coupling agent NDZ-311 and mix and stir for 2 h. Send to a twin-screw granulator for granulation to obtain inner layer pellets.

[0064] S2, polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride were dried at 65° C. in vacuum for 11 h to remove moisture and impurities, toughening fibers were added and mixed for 2 h, and then sent to a twin-screw granulator for granulation to obtain outer layer granules;

[0065] S3, the inner layer pellets and the outer layer pellets are respectively transported to the two feed ports of the co-extrusion film blowing system for extrusion and film blowing to obtain an environmentally friendly, non-toxic, biodegradable garbage bag (such as Figure 1 as shown).

[0066] The above-mentioned co-extrusion film blowing system includes two single-screw extruders and an A / B / A film blowing head. The melt flow of the outer layer pellets is divided into two parts, which are combined with the inner layer pellets before the film blowing die to obtain a three-layer composite film; the heating zone temperature of the co-extrusion film blowing system is 170°C, and the temperature of the film blowing head is 150°C. Comparative Example 1

[0067] The invention discloses an environmentally friendly, non-toxic and biodegradable garbage bag. The raw materials thereof include: 85 kg of polyethylene, 110 kg of nano calcium carbonate with a particle size of 60-80 nm, 3 kg of iron stearate, 3 kg of chitosan, 3 kg of magnesium stearate, 2 kg of polyethylene wax, 2 kg of titanate coupling agent NDZ-311, 20 kg of corn starch, 3 kg of polyaspartic acid, 35 kg of polylactic acid, 50 kg of polybutylene terephthalate-adipate, 10 kg of polybutylene succinate, 1.2 kg of maleic anhydride and 10 kg of toughening fiber.

[0068] The toughened fiber was prepared by the following specific operation: chitosan oligosaccharide was added to water, stirred evenly at 68°C, sodium methyl propylene sulfonate was added thereto and stirred for 15 minutes, potassium persulfate was added, the pH value of the system was adjusted to 7-7.8, stirred for 2.5 hours, microcrystalline cellulose was added, stirred at 95°C for 20 minutes, filtered, washed to neutral, and freeze-dried. The mass ratio of chitosan oligosaccharide, sodium methyl propylene sulfonate, potassium persulfate, and microcrystalline cellulose was 10:1.5:0.05:15.

[0069] The method for preparing the above-mentioned environmentally friendly, non-toxic and biodegradable garbage bag comprises the following steps:

[0070] S1. The corn starch and polyaspartic acid were vacuum dried, polyethylene, nano calcium carbonate, iron stearate, chitosan, magnesium stearate, polyethylene wax, and titanate coupling agent NDZ-311 were added, mixed and stirred for 2 hours, and sent to a twin-screw granulator for granulation to obtain inner layer granules;

[0071] S2, polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride were dried at 65° C. in vacuum for 11 h to remove moisture and impurities, toughening fibers were added and mixed for 2 h, and then sent to a twin-screw granulator for granulation to obtain outer layer granules;

[0072] S3, conveying the inner layer pellets and the outer layer pellets to two feed ports of the co-extrusion film blowing system respectively for extrusion film blowing.

[0073] The above-mentioned co-extrusion film blowing system includes two single-screw extruders and an A / B / A film blowing head. The melt flow of the outer layer pellets is divided into two parts, which are combined with the inner layer pellets before the film blowing die to obtain a three-layer composite film; the heating zone temperature of the co-extrusion film blowing system is 170°C, and the temperature of the film blowing head is 150°C. Comparative Example 2

[0074] The invention discloses an environmentally friendly, non-toxic and biodegradable garbage bag. The raw materials thereof include: 85 kg of polyethylene, 110 kg of nano calcium carbonate with a particle size of 60-80 nm, 3 kg of iron stearate, 3 kg of chitosan, 3 kg of magnesium stearate, 2 kg of polyethylene wax, 2 kg of titanate coupling agent NDZ-311, 20 kg of corn starch, 3 kg of acrylamide, 1.5 kg of polyvinyl alcohol, 50 g of N,N-methylenebisacrylamide, 5 g of ammonium persulfate, 3 kg of polyaspartic acid, 35 kg of polylactic acid, 50 kg of polybutylene terephthalate-adipate, 10 kg of polybutylene succinate, 1.2 kg of maleic anhydride, 3.77 kg of chitosan oligosaccharide and 5.65 kg of microcrystalline cellulose.

[0075] The method for preparing the above-mentioned environmentally friendly, non-toxic and biodegradable garbage bag comprises the following steps:

[0076] S1. Add corn starch to 150 kg of water and ultrasonically treat for 90 min at an ultrasonic frequency of 12 kHz. Pass nitrogen for degassing. Add acrylamide, polyvinyl alcohol, N,N-methylenebisacrylamide, ammonium persulfate, and polyaspartic acid thereto. Stir at 75 ° C for 2 h. Filter. Wash with deionized water. Vacuum dry. Add polyethylene, nano calcium carbonate, iron stearate, chitosan, magnesium stearate, polyethylene wax, and titanate coupling agent NDZ-311 and mix and stir for 2 h. Send to a twin-screw granulator for granulation to obtain inner layer pellets.

[0077] S2, polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride were vacuum dried at 65° C. for 11 h to remove moisture and impurities, chitosan oligosaccharide and microcrystalline cellulose were added and mixed for 2 h, and then sent to a twin-screw granulator for granulation to obtain outer layer granules;

[0078] S3, conveying the inner layer pellets and the outer layer pellets to two feed ports of the co-extrusion film blowing system respectively for extrusion film blowing.

[0079] The above-mentioned co-extrusion film blowing system includes two single-screw extruders and an A / B / A film blowing head. The melt flow of the outer layer pellets is divided into two parts, which are combined with the inner layer pellets before the film blowing die to obtain a three-layer composite film; the heating zone temperature of the co-extrusion film blowing system is 170°C, and the temperature of the film blowing head is 150°C.

[0080] The following performance tests were performed on the garbage bags obtained in Example 5 and Comparative Examples 1-2:

[0081] 1. Refer to GB / T 1040.4-2006 "Determination of tensile properties of plastics Part 4: Test conditions for isotropic and orthotropic fiber reinforced composites" for tensile strength test, with a tensile speed of 20 mm / min.

[0082] 2. Refer to CJ / T 234-2006 "High-density polyethylene geomembrane for landfill" for puncture resistance test.

[0083] 3. Place weights of different weights into each group of garbage bags until the bags burst, and record the weight.

[0084] like Figures 2 to 4 As shown, the tensile strength, puncture strength and load-bearing quality of the garbage bag obtained in Example 5 are all the highest, which are better than those in Comparative Examples 1-2 (P < 0.05).

[0085] In view of the fact that the garbage bag obtained in Example 5 has the best performance, the present application uses the garbage bag obtained in Example 5 to measure the final aerobic biodegradability of the material under controlled composting conditions.

[0086] Test basis and method: GB / T 19277.1-2011 "Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions by measuring the released carbon dioxide - Part 1: General method".

[0087] Among them, the reference material is microcrystalline cellulose (column chromatography FCC), which is white or off-white powder and purchased from Sinopharm Chemical Reagent Co., Ltd. The test materials and reference materials were mixed with soil and aerobic composted for 150 days. Figure 5As shown in Figure 1, after 150 days of compost degradation, Figure 6 shown.

[0088] Pre-test treatment: Screen through a 0.5 cm sieve to remove impurities and inert substances. Then conduct the test at a constant temperature of 58 ± 2 ° C, weak light, and without any steam that may affect the growth of microorganisms.

[0089] The number of reaction containers is as follows: 3 containers for test materials, 3 containers for reference materials, and 3 blank containers.

[0090] The cumulative carbon dioxide production and biodegradation percentage during the test are shown in Table 1-15:

[0091] Table 1 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 1st to 10th day of degradation

[0092]

[0093] Table 2 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 11th to 20th day of degradation

[0094]

[0095] Table 3 Summary of the cumulative carbon dioxide production and biodegradation rate of blank containers, containers containing reference materials and containers containing test materials on the 21st to 30th day of degradation

[0096]

[0097] Table 4 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 31st to 40th day of degradation

[0098]

[0099] Table 5 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 41st to 50th day of degradation

[0100]

[0101] Table 6 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials, and containers containing test materials on the 51st to 60th day of degradation

[0102]

[0103] Table 7 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 61st to 70th day of degradation

[0104]

[0105] Table 8 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 71st to 80th day of degradation

[0106]

[0107] Table 9 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 81st to 90th day of degradation

[0108]

[0109] Table 10 Summary of the cumulative carbon dioxide production and biodegradation rate of blank containers, containers containing reference materials and containers containing test materials on the 91st to 100th day of degradation

[0110]

[0111] Table 11 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 101st to 110th day of degradation

[0112]

[0113] Table 12 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 111th to 120th day of degradation

[0114]

[0115] Table 13 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 121st to 130th day of degradation

[0116]

[0117] Table 14 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 131st to 140th day of degradation

[0118]

[0119] Table 15 Summary of the cumulative carbon dioxide production and biodegradation rates of blank containers, containers containing reference materials and containers containing test materials on the 141st to 150th day of degradation

[0120]

[0121] Plot the data in the above table into a graph, such as Figure 7 and Figure 8 shown.

[0122] According to the above table, the garbage bags obtained in Example 5 were degraded by aerobic composting for 150 days, and their average biodegradation rate reached 80.9%, far exceeding the index requirement of ≥60%, and their relative decomposition rate reached 92.1%, also exceeding the index requirement of ≥90%, proving that the garbage bags obtained in the present invention have excellent biodegradability.

[0123] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An environmentally friendly, non-toxic, biodegradable garbage bag, characterized in that: The raw materials include, by mass: 80-90 parts of polyethylene, 100-120 parts of nano calcium carbonate, 1-5 parts of photosensitizer, 1-5 parts of chitosan, 1-5 parts of lubricant, 1-3 parts of dispersant, 1-3 parts of coupling agent, 10-30 parts of starch, 1-5 parts of acrylamide, 1-2 parts of polyvinyl alcohol, 0.01-0.1 parts of crosslinking agent, 0.001-0.01 parts of initiator, 1-5 parts of polyaspartic acid, 30-40 parts of polylactic acid, 40-60 parts of polybutylene terephthalate-adipate, 5-15 parts of polybutylene succinate, 0.1-2 parts of maleic anhydride, and 5-15 parts of toughening fiber; The raw materials of toughening fiber include: oligosaccharide, sodium methyl propylene sulfonate, potassium persulfate, microcrystalline cellulose, and the mass ratio of oligosaccharide, sodium methyl propylene sulfonate, potassium persulfate, microcrystalline cellulose is 5-15:1-2:0.01-0.1:10-20; Prepared by the following steps: S1. Add starch to water and ultrasonically treat for 1-2 hours, introduce nitrogen for degassing, add acrylamide, polyvinyl alcohol, crosslinking agent, initiator, polyaspartic acid, stir at 70-80° C. for 1-3 hours, filter, wash with water, vacuum dry, add polyethylene, nano calcium carbonate, photosensitizer, chitosan, lubricant, dispersant, coupling agent, mix and stir for 1-3 hours, and granulate to obtain inner layer granules; S2, vacuum drying polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride for 10-12 hours to remove moisture and impurities, adding toughening fiber and mixing for 1-3 hours, and granulating to obtain outer layer pellets; S3, conveying the inner layer pellets and the outer layer pellets to two feed ports of the co-extrusion film blowing system respectively for extrusion film blowing.

2. The environmentally friendly, non-toxic, biodegradable garbage bag according to claim 1, characterized in that: The particle size of nano calcium carbonate is 60-80nm.

3. The environmentally friendly, non-toxic, biodegradable garbage bag according to claim 1, characterized in that: The photosensitizer is at least one of ferric eleostearate, benzophenone and ferric stearate.

4. The environmentally friendly, non-toxic, biodegradable garbage bag according to claim 1, characterized in that: The lubricant is at least one of calcium stearate, zinc stearate and magnesium stearate.

5. The environmentally friendly, non-toxic, biodegradable garbage bag according to claim 1, characterized in that: The dispersant is erucamide and / or polyethylene wax.

6. The environmentally friendly, non-toxic, biodegradable garbage bag according to claim 1, characterized in that: The coupling agent is at least one of a titanate coupling agent, an aluminate coupling agent and a silane coupling agent.

7. The environmentally friendly, non-toxic, biodegradable garbage bag according to claim 1, characterized in that: The crosslinking agent is N,N-methylenebisacrylamide, and the initiator is ammonium persulfate.

8. The environmentally friendly, non-toxic, biodegradable garbage bag according to claim 1, characterized in that: The toughened fiber is prepared by the following specific operation: adding oligosaccharides into water, stirring evenly at 60-75°C, adding sodium methyl methacrylate sulfonate thereto and continuing stirring for 10-20 minutes, adding potassium persulfate, adjusting the pH value of the system to 7-7.8, stirring for 1-4 hours, adding microcrystalline cellulose, stirring at 90-100°C for 10-30 minutes, filtering, washing to neutrality, and freeze-drying.

9. A method for preparing an environmentally friendly, non-toxic, biodegradable garbage bag as claimed in any one of claims 1 to 8, characterized in that: The steps include: S1. Add starch to water and ultrasonically treat for 1-2 hours, introduce nitrogen for degassing, add acrylamide, polyvinyl alcohol, crosslinking agent, initiator, polyaspartic acid, stir at 70-80° C. for 1-3 hours, filter, wash with water, vacuum dry, add polyethylene, nano calcium carbonate, photosensitizer, chitosan, lubricant, dispersant, coupling agent, mix and stir for 1-3 hours, and granulate to obtain inner layer granules; S2, vacuum drying polylactic acid, polybutylene terephthalate-adipate, polybutylene succinate, and maleic anhydride for 10-12 hours to remove moisture and impurities, adding toughening fiber and mixing for 1-3 hours, and granulating to obtain outer layer pellets; S3, conveying the inner layer pellets and the outer layer pellets to two feed ports of the co-extrusion film blowing system respectively for extrusion film blowing.

10. The method for preparing the environmentally friendly, non-toxic and biodegradable garbage bag according to claim 9, characterized in that: The co-extrusion film blowing system includes two single-screw extruders and an A / B / A film blowing die. The melt flow of the outer layer pellets is divided into two parts, which are combined with the inner layer pellets before the film blowing die to obtain a three-layer composite film. The heating zone temperature of the co-extrusion film blowing system is 160-180°C, and the temperature of the film blowing die is 145-155°C.

Citation Information

Patent Citations

  • Starch biodegradable film and production method thereof

    CN114736437A

  • Environment-friendly garbage bag and preparation method thereof

    CN116535823A